Perbedaan Karakteristik Koloni Bakteri Staphylococcus aureus Pada Media Agar Darah Domba dan Media Agar Darah Manusia - Nurhidayanti, Nurhidayanti; Sari, Refina Ratna (Jurnal Analis Kesehatan, 2022)
Sheep blood agar is the standard medium for culturing pathogenic bacteria, as an alternative, human blood agar media is used as an alternative from transfusion. This study aims to observe the differences in the characteristics of Staphylococcus aureusbacteria on sheep blood agar media and human blood agar media which was carried out at BBLK Palembang. This type of research was conducted experimentally with a total sample of 32 and analyzed statistically. Bacterial suspension derived from the pure strain of Staphylococcus aureus ATCC 25923. The colony characteristics were observed macroscopically including colony morphology, colony number and colonydiameter. The average value of the number of colonies of Staphylococcus aureus bacteria on sheep blood agar and human blood agar media were 173 and 148, while the colony diameters were 2.5 mm and 2 mm, respectively. The results of the research data on the number of colonies were tested with an unpaired T test with p value = 0.001 and colony diameter data was tested with the Mann Whitney alternative test with p = 0.031, which means that there is a statistically significant difference between the characteristics of the Staphylococcus aureusbacteria colony on the media. sheep blood agar and human blood agar media.